Del Corazon / Aida Azmera Abd. Latif ... [et al.] - Abd. Latif, Aida Azmera; Othman, Arina; Din, Dalira; Salim, Fatimah Maneesa; Khamis, Hariswani (2003)
Del Corazon is a business that selling a multiple souvenirs and providing a wrapping services. It has its own administration that is important part in making a business plan. It is about the administration of the business and it can show us the skillful of entrepreneur in managing and administrating the business. In the business, we have our own mission and objectives that should be achieved in a specific period of time. This is made in order to ensure the business running could make the demand of the customers can be fulfilled. All the important skill and expertise in administration is use to make the business more dynamic and successful. The administrative also to manage the management systems effective and systematically. In terms of contract of services, we should follow the rules and regulation of the partnership. There is a hierarchy in organization structure to make all the management become more clearly, orderly and easy to understand. All the partnership have their own task and responsibility to be fulfilled. The budget in the administration plan is prepared to record all the expenses made. So that, indirectly it can help to identify the profits and loses in the business.